The Impact of Shopping Values on E-Satisfaction and Shopping Wellbeing: A South African Perspective - Valerie Natalie Mbulo; Tinashe Tsungai Raphael Ndoro (Journal of Management and Entrepreneurship Research, 2024)
Objective: Shopping well-being has continued to be a fundamental construct in retail shopping research. However, marketers seek to understand the factors that enhance shopping well-being for online consumers in the fast-growing era of e-commerce. This study sought to investigate the impact of shopping values (hedonic and utilitarian) and e-satisfaction on shopping well-being within the South African context. Research Design & Methods: The study used a cross-sectional quantitative research design. Using convenience sampling, online survey questionnaires were administered to collect the data from South African consumers who engage in online shopping. Descriptive analysis and multiple regression analysis were used to analyse the data. Findings: The findings of the study indicated hedonic shopping values had a positive impact on shopping well-being. On the other hand, it was found that utilitarian shopping values and e-satisfaction had no positive impact on shopping wellbeing. Implications and Recommendations: From these findings, web-based shopping managers can construct online shopping environments that support hedonic shopping values in order to ensure that consumers shopping online experience shopping wellbeing. Contribution & Value Added: The study adds value to marketing practitioners and businesses that seek to ensure that consumers engaging in online shopping experience satisfaction and wellbeing within the growing e-commerce industry in South Africa and other emerging economies.